Experimental study on small strain dynamic characteristics of citric acid modified magnesium oxysulfate cement solidified engineering waste soil - Na Li; Xinyu Yan; Yifang Song; Wei Wang; Ping Jiang; Xianwen Huang; Guoxiong Mei (Results in Engineering)
To build an environmental protection society and improve the resource utilization rate of engineering residue, this paper uses magnesium oxysulfate cement instead of ordinary Portland cement solidified engineering residue, and use the additive citric acid(CA). In geotechnical engineering, the subgrade is subjected to cyclic dynamic load for a long time.The dynamic shear modulus and damping ratio are fundamental parameters governing soil behavior under cyclic loading. To date, most of the existing researches focus on the static mechanical properties of CA-modified magnesium oxysulfate cement(MSC), few studies have been reported on the dynamic properties under cyclic load. Therefore, the resonance column testing was conducted to evaluate how varying CA content and confining pressure influence the dynamic shear modulus(G) and damping ratio (D) of engineering residue solidified with CA.The results show that: 1)When the citric acid content is 3 %, the dynamic shear modulus of the sample is the largest, and the damping ratio is the smallest. The dynamic shear modulus demonstrates a positive correlation with confining pressure, whereas the damping ratio shows an inverse relationship.2)The normalized variations of both G/Gmax and D with shear strain show excellent agreement with the Hardin-Drnevich model, demonstrating appropriate normalization behavior.3)The microscopic test results showed that citric acid reacted with magnesium oxysulfate cement to form 5·1·7 phases (5Mg(OH)2·MgSO4·7H2O), which made the soil structure more dense. These outcomes enable more accurate prediction of dynamic soil responses in eco-friendly ground improvement projects, particularly for seismic-resistant foundations and roadbed under traffic loads.